Quantification of Mental and Physiological Workload Associated with two Specialised Military Running Events on Different Terrains - Chatterjee, Tirthankar; Bhattacharyya, Debojyoti; Yadav, Angad; Arya, Kavita; Meena, Roshani; Pal, Madhusudan (Defence Life Science Journal, 2022)
Intense training regimes are practiced across military facilities to develop soldiers’ mental and physical abilities to meet the demands of modern-day warfare. Two short-duration military runs through the jungle and flat natural tracks were selected to quantify their mental and physiological workloads and explore track-specific differences. Two groups of healthy Indian soldiers (n=43 and 30; similar age, height, and weight) participated in time-bound 2.4 km runs on the jungle and flat natural tracks. Physiological variables, speed, and elevation with environmental parameters like temperature and humidity were recorded throughout the exercises. Subjective responses through NASA-TLX questionnaires were collected after the exercises. Mann-Whitney ‘U’ test was applied to find out the level of significance between groups.Physiological demands of runs on the jungle and flat natural track were similar (heart rate- 178.9 and 178.4 b/min; breathing rate- 42.0 and 46.6 breaths/min respectively; body temperature- 37.6℃ for both groups). The run on the jungle track needed a lower peak acceleration of 2.5 g (2.9 g on the flat track) and a higher variation in speed (4-16 knots). Participants expressed significantly high responses after the run on the jungle track. Run on the jungle track was physically intense, required adjustments in speed and acceleration to negotiate with the natural obstacles like uneven terrain and slippery surfaces. Besides this, environmental heat and higher humidity probably led to an increase in mental workload. The run on the flat natural track needed steady physical effort, fewer mechanical adjustments, and showed lower subjective responses.